2015
DOI: 10.1111/ane.12540
|View full text |Cite
|
Sign up to set email alerts
|

High-dose statin therapy and risk of intracerebral hemorrhage: a meta-analysis

Abstract: Statin plays a major role in the primary and secondary prevention of cardiovascular disease (CVD). Inconsistent findings in the studies have been observed toward the risk of intracerebral hemorrhage (ICH) using higher dose of statin. To examine this issue, we performed a meta-analysis of randomized controlled trials (RCTs) to assess the association between higher dose of various statins and risk of ICH among patients with CVD. Literature was searched for studies published before June 10, 2015, using electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…[14,18,19] A previous meta-analysis with 7 RCTs included have found that atorvastatin 80 mg/d can increase the risk of intracerebral hemorrhage. [35] In this review, all the included studies have taken atorvastatin 20 mg/d as the intervention, and no studies have reported related adverse events. In the future, more high-quality RCTs, with dosage and duration analysis, taking atorvastatin as an adjunct to surgery or as a monotherapy, are needed when assessing the efficacy of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…[14,18,19] A previous meta-analysis with 7 RCTs included have found that atorvastatin 80 mg/d can increase the risk of intracerebral hemorrhage. [35] In this review, all the included studies have taken atorvastatin 20 mg/d as the intervention, and no studies have reported related adverse events. In the future, more high-quality RCTs, with dosage and duration analysis, taking atorvastatin as an adjunct to surgery or as a monotherapy, are needed when assessing the efficacy of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, clinical trials investigating statins as the primary cardiovascular disease prevention strategy have yielded inconsistent results for ICH risk. [4][5][6] Results from several observational studies evaluating data from a large number of ICH cases also reported inverse associations between lipid levels and ICH risk. The Genetic and Environmental Risk Factors for Hemorrhagic Stroke (GERFHS) study reported a one third lower ICH risk among study participants with a medical history of hypercholesterolemia.…”
mentioning
confidence: 93%
“…A previous study showed that statin users had a higher risk of gastrointestinal hemorrhage than other chronic medication users (42). Moreover, in patients with CVD, a meta-analysis of seven RCTs showed that a higher dose of statins was associated with a risk of intracranial hemorrhage (ICH) (43). Previous studies also showed that a lower serum LDL-C may be associated with a higher risk of ICH (44,45).…”
Section: Discussionmentioning
confidence: 99%